The bidirectional nature of microbiome-epithelial cell interactions. (August 2020) - Solis, Angel G; Klapholz, Max; Zhao, Jingru; Levy, Maayan
Abstract : The biogeography of the mammalian intestine is remarkable in that a vast microbial consortium exists inside the organism, surrounded by intestinal epithelial cells. The microbiome and the intestinal epithelium have developed a complex network of interactions that maintain intestinal homeostasis. We now recognize that functions of the epithelium are compartmentalized in specific intestinal epithelial cell subtypes. Furthermore, we are beginning to understand the ways in which microbes and their metabolic products impact the specific epithelial subsets. Here, we survey the mechanisms utilized by the microbiome to regulate intestinal epithelial function, and inversely, how different epithelial cell subtypes cooperate in regulating the microbiome.